The Path to Eldership: Results From a Contemporary Indigenous Australian Community. (12th May 2021) - Eades, Owen; Toombs, Maree R; Cinelli, Renata; Easton, Caitlin; Hampton, Ron; Nicholson, Geoffrey C; McCabe, Marita P; Busija, Lucy
Abstract: Background and Objectives: Traditionally, Elders have held a unique social position within Indigenous Australian communities. This study aimed to identify the characteristics of Indigenous Elders that distinguish them from other people in their community. Research Design and Methods: Using a community-based participatory research approach, the study was conducted in a regional Indigenous community in Southeast Queensland. The design and data collection methods were informed through a community forum, known as a "Yarning Circle." One-on-one semistructured interviews and focus groups with community members were carried out by Indigenous researchers. Data were analyzed in NVivo software, using thematic analysis (TA), with themes derived directly from data. Results: Fifty individuals participated in the study. The participants' median age was 45 years (range 18–76 years) and 31 (62%) were female. TA identified 3 overarching themes related to Elders' attributes: (a) distinguishing characteristics of Elders (subthemes of respect, leadership, reciprocity, life experience, approachability, connection to traditional culture, and transmitting knowledge through generations); (b) how one becomes an Elder (earnt eldership, permanency of eldership, mentors and role models, age); and (c) threats to Elders' influence (intergenerational gap, community disconnect, and cultural trauma). Discussion and Implications: Our results build a greater understanding of the contemporary role of Indigenous Australian Elders, which will inform the development of future interventions directed at strengthening Elders' role in their communities.